Iterative Method for Non-Stationary Mixed Variational Inequalities - Salahuddin (Discontinuity, Nonlinearity, and Complexity, 2026)
We consider a non-stationary mixed variational inequality problem involving an integrable mapping and a convex function, where only approximation sequences are known instead of exact values of the cost mapping and function, and feasible set. We apply a descent method and partial penalization to prove the convergence is attained without concordance of penalty, accuracy, and approximation parameters under coercivity type conditions.